Influence of nano-silica and -metakaolin on the hydration characteristics and microstructure of air-cooled slag-blended cement mortar. Issue 5 (3rd September 2017) - Abdel Gawwad, H. A.; Abd El-Aleem, S.; Faried, A. S.
Abstract: This study aims at enhancing the hydration characteristics and microstructure of cement mortar (CM) containing ground air-cooled slag (ACS), using nano-silica (NS) and nano-metakaolin (NMK) powder. Firstly, ordinary Portland cement (OPC) was replaced by 0, 5, 10, 15, and 20 wt.% ground ACS. CM was designed at 3:1 of sand: OPC/ACS ratio. The water to cement (W/C) ratio was adapted at 0.47. It was found that the CM containing 5 wt.% ACS showed the highest compressive strength and free lime content at 90-day of hydration. Meanwhile, significant reduction in compressive strength and free lime values was observed in case of CM containing 20 wt.% ACS. Different NS and NMK percentages (2, 4, 6 and 8 wt.%) were individually added to CM containing 20 wt.% ACS, in order to enhance its chemical and physico-mechanical properties. The results showed that the addition of 6 wt.% NS and 4 wt.% NMK led to increase the compressive strength of ACS-blended CM by 116 and 42%, respectively, compared to the control sample (without ACS). The hydration products were identified using X-ray diffraction, differential thermal analysis, thermogravimetric analysis, and scanning electron microscopy.